Protein Intake and Bone Health in the Elderly - Götz, Helene Josefa; Amrein, Karin (Osteologie, 2024)
Protein plays an important role in muscle and bone metabolism. This is of great importance for optimal bone health, especially in the elderly, in sarcopenia and osteoporosis. Adequate protein intake is a prerequisite for optimal musculoskeletal health and efficient strength training. Protein is one of the macronutrients and besides calcium the most abundant structural component of our musculoskeletal system. However, elderly subjects often consume too little protein. In 2017, the revised reference values in the D-A-CH region were increased for adults>65 years to 1.0 g protein/kg (ideal) body weight [BW]/ day and ESPEN even advocates for an intake of 1.0–1.5 g protein/kg BW/ day. Many elderly people, especially women do not meet these targets. In our experience, there is a fundamental misconception that protein needs can only be met consuming animal products. Many studies have investigated whether sufficient protein intake has a positive effect on bone. In this short review, the importance of protein for bone and the problem of inadequate protein intake in sarcopenia will be discussed and the most relevant clinical guidelines and studies will be presented. For practical use, we give examples of omnivore and vegetarian meal plans and important protein sources (plant and animal origin) are given. Usually, the minimal demands can easily be met with simple nutritional advice. Sometimes however, additional protein supplements (often liquids, puddings, powders) are needed, especially in nursing home residents, and when poor appetite or dysphagia impair appropriate caloric and protein intake.
Keywords: protein; malnutrition; bone; osteoporosis; veganism